A Review of Some of The Treatments of Oil-Contaminated Soils (University of Thi-Qar Journal for Engineering Sciences, 2023)
Soil characteristics are impacted by the nearness to the contamination sources. Accidental oozes and leaks of crude-oil are frequent occurrences that change the shear resistance and stress-strain behavior of soils by incompletely or totally replacing the soil pore liquid with oil. Soil contamination has become a main objective of the research in several conditions; this issue arises from the effect of previous and present industrial activities; taking the essential solutions scientifically towards these issues have become an urgent case that must be carefully studied. Numerous methods of remediation and stabilization of oil-contaminated soils have been applied during the preceding period due to their influence on the potential for collapse. Soil Stabilization is the modification of soils to improve their engineering properties. Chemical stabilization techniques have been one of the most adopted methods for enhancing the geotechnical properties of oil-contaminated soils. To realize the importance of using various additives that can improve the soil polluted with oil, like cement, lime, fly ash, and others, It is necessary to study the mechanical behavior of soils contaminated with oil and treated with different materials. This paper aims to review the investigations work on different types of soil contaminated with oil and to enhance it with various additions